Developing commotio cordis injury metrics for baseball safety: unravelling the connection between chest force and rib deformation to left ventricle strain and pressure. Issue 3 (17th February 2022) - Dickey, Grant J.; Bian, Kewei; Khan, Habib R.; Mao, Haojie
Abstract: Commotio cordis is a sudden death mechanism that occurs when the heart is impacted during the repolarization phase of the cardiac cycle. This study aimed to investigate commotio cordis injury metrics by correlating chest force and rib deformation to left ventricle strain and pressure. We simulated 128 chest impacts using a simulation matrix which included two initial velocities, 16 impact locations spread across the transverse and sagittal plane, and four baseball stiffness levels. Results showed that an initial velocity of 17.88 m/s and an impact location over the left ventricle was the most damaging setting across all possible settings, causing the most considerable left ventricle strain and pressure increases. The impact force metric did not correlate with left ventricle strain and pressure, while rib deformations located over the left ventricle were strongly correlated to left ventricle strain and pressure. These results lead us to the recommendation of exploring new injury metrics such as the rib deformations we have highlighted for future commotio cordis safety regulations.